The Effect of Website Quality and E-Trust on E-Satisfaction and E-Loyalty of suara.com Website Users - Chaerani, Rizka (Syntax Literate, 2025)
The development of online media in Indonesia has experienced rapid progress along with the development of information and communication technology that continues to grow so that reading news through websites has become a current trend that then leaves print media such as newspapers or magazines. This creates competition in the digital media industry. This study aims to determine the effect of website quality and e-trust on e-satisfaction and e-loyalty of suara.com website users. This study was conducted quantitatively with a causal study approach on 176 research respondents who were Suara.com users domiciled in Jabodetabek. The results of the study showed that website quality and e-trust had a significant and positive effect on e-satisfaction, and website quality, e-trust and e-satisfaction had a significant and positive effect on e-loyalty. These findings provide a foundation for future research to investigate other influencing variables such as user engagement, personalization, or mobile experience, and to extend the model’s applicability to other online media platforms or regions.